Compound a, a dissociated glucocorticoid receptor modulator, inhibits t-bet (th1) and induces gata-3 (th2) activity in immune cells - Liberman, A.C. (2012)
Background: Compound A (CpdA) is a dissociating non-steroidal glucocorticoid receptor (GR) ligand which has anti-inflammatory properties exerted by down-modulating proinflammatory gene expression. By favouring GR monomer formation, CpdA does not enhance glucocorticoid (GC) response element-driven gene expression, resulting in a reduced side effect profile as compared to GCs. Considering the importance of Th1/Th2 balance in the final outcome of immune and inflammatory responses, we analyzed how selective GR modulation differentially regulates the activity of T-bet and GATA-3, master drivers of Th1 and Th2 differentiation, respectively. Results: Using Western analysis and reporter gene assays, we show in murine T cells that, similar to GCs, CpdA inhibits T-bet activity via a transrepressive mechanism. Different from GCs, CpdA induces GATA-3 activity by p38 MAPK-induction of GATA-3 phosphorylation and nuclear translocation. CpdA effects are reversed by the GR antagonist RU38486, proving the involvement of GR in these actions. ELISA assays demonstrate that modulation of T-bet and GATA-3 impacts on cytokine production shown by a decrease in IFN-γ and an increase in IL-5 production, respectively. Conclusions: Taken together, through their effect favoring Th2 over Th1 responses, particular dissociated GR ligands, for which CpdA represents a paradigm, hold potential for the application in Th1-mediated immune disorders. © 2012 Liberman et al.